HUBUNGAN ANTARA DRY EYES TERHADAP KEBIASAAN MEROKOK: TINJAUAN SISTEMATIS - Magdalena Purba, Elizabeth (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Dry eyes, also known as dry eye disease (DED), dry eye syndrome, and keratoconjunctivitis sicca (KCS), are among the most common reasons people visit an eye doctor. Other names for dry eyes include: dry eye disease (DED), dry eye syndrome, and keratoconjunctivitis sicca (KCS). Environmental factors that may have a role include, but are not limited to, exposure to irritants such as chemical vapors, cigarette smoke, pollution, or low humidity. Smoking cigarettes, which is a modifiable risk factor for a wide range of illnesses including vascular disease, lung cancer, and chronic obstructive pulmonary disease, has been explored as a potential risk factor for DED in a number of population-based studies. These studies have found that smoking cigarettes is associated with an increased risk of DED. Smoking cigarettes is another element that can contribute to the development of DED. It's possible that smoking has nothing to do with the risk of DED. There is a lack of agreement regarding the impact that smoking has on the danger of developing DED as a result of the contradictory research. Although a number of recent studies have revealed that there is a preventive impact of smoking on DED, the overall damage that smoking does to one's health balances the protective benefit that continuing smoking has on DED.